Adab as an Operational Pedagogical Principle: Intercultural Alignment in Arabic Language Teaching at a Tahfīẓ Pesantren in West Java, Indonesia - Akhmad Ridlo; Didi Suryadi; Mohamad Zaka Al Farisi (Fakultas Tarbiyah dan Ilmu Keguruan, Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2026)
Adab, the Islamic ethical orientation governing the conduct of knowledge, functions as an operational pedagogical principle shaping Arabic language teaching in a tahfīẓ pesantren in West Java, Indonesia. Using a qualitative case study design, the research was conducted at a purposively selected institution in which Qur’anic memorization constitutes the primary educational commitment. Participants included one institutional leader, two Arabic language teachers, and fourteen students distributed across junior and senior learning groups. Data were generated through 12 structured classroom observation sessions, semi-structured individual interviews, and institutional document analysis; thematic analysis, following Braun & Clarke’s (2006) six-phase procedure, yielded three analytical themes mapped directly to the three research questions. The findings demonstrate that Adab is not merely a background value but is explicitly invoked as a principle governing real-time instructional decisions, including lesson scope, pacing calibration, and the management of cognitive demands relative to students’ memorization responsibilities. At the junior level, Adab-oriented restraint manifests through visual scaffolding, tikrār (repetition-based memorization practice), and intensive teacher mediation; at the senior level, it shapes the integration of classical grammatical traditions with analytical textual interpretation. Framed through intercultural education theory (Bennett, 1993, 2017; Byram, 1997, 2021; Holliday, 2011; Kramsch, 1993, 2021), these instructional adaptations are theorized as intercultural pedagogical alignment — teachers’ principled, culturally informed negotiation between communicative language pedagogies and the institution's memorization-centered learning culture. Three specific contributions are advanced: (1) an empirical account of Adab as documentable classroom-level practice rather than abstract norm; (2) the concept of intercultural pedagogical alignment as a new analytical category for value-oriented educational settings; and (3) a reinterpretation of the absence of Arabic immersion environments as a cognitively rational, ethically grounded institutional choice.